Viral infection of an estuarine Synechococcus influences its co-occurring heterotrophic bacterial community in the culture - Man, Hongcong; Liu, Binbin; Zheng, Hongrui; Liu, Jihua; Xu, Yongle; Chen, Feng (Frontiers in Microbiology, 2024)
Viruses are infectious and abundant in the marine environment. Viral lysis of host cells releases organic matter and nutrients that affect the surrounding microbial community. Synechococcus are important primary producers in the ocean and they are subject to frequent viral infection. In the laboratory, Synechococcus cultures are often associated with bacteria and such a co-existence relationship appears to be important to the growth and stability of Synechococcus. However, we know little about how viral lysis of Synechococcus affects the co-existing bacteria in the culture. This study investigated the influence of viral infection of Synechococcus on co-occurring bacterial community in the culture. We analyzed the community composition, diversity, predicted functions of the bacterial community, and its correlations with fluorescent dissolved organic matter (FDOM) components and nutrients of bacterial community after introducing a cyanophage to the Synechococcus culture. Cyanophage infection altered the bacterial community structure and increased the bacterial diversity and richness. Increased bacterial groups such as Bacteroidetes and Alphaproteobacteria and decreased bacterial groups such as Gammaproteobacteria were observed. Moreover, cyanophage infection reduced bacterial interactions but enhanced correlations between the dominant bacterial taxa and nutrients. Unique FDOM components were observed in the cyanophage-added culture. Fluorescence intensities of FDOM components varied across the cyanophage-infection process. Decreased nitrate and increased ammonium and phosphate in the cyanophage-added culture coupled with the viral progeny production and increased substance transport and metabolism potentials of the bacterial community. Furthermore, increased potentials in methane metabolism and aromatic compound degradation of the bacterial community were observed in the cyanophage-added culture, suggesting that cyanophage infections contribute to the production of methane-related compounds and refractory organic matter in a microcosm like environment. This study has the potential to deepen our understanding of the impact of viral lysis of cyanobacteria on microbial community in the surrounding water.